2016
DOI: 10.1111/psyp.12700
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic insomnia have selective impairments in memory that are modulated by cortisol

Abstract: Memory impairment is a frequent complaint in insomniacs; however, it is not consistently demonstrated. It is unknown whether memory impairment in insomniacs involves neuroendocrine dysfunction. The participants in this study were selected from the clinical setting and included 21 patients with chronic insomnia disorder (CID), 25 patients with insomnia and comorbid depressive disorder (CDD), and 20 control participants without insomnia. We evaluated spatial working and reference memory, object working and refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 43 publications
3
35
0
1
Order By: Relevance
“…Increasing findings have shown that CID patients possess significantly objective memory impairment [3-5, 23, 24]. Our current study once again demonstrated that CID patients had SWM and ORcM impairments (see Table 2), consistent with our previous findings [5,12]. Nevertheless, little is known about the mechanism of memory impairment in the CID patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Increasing findings have shown that CID patients possess significantly objective memory impairment [3-5, 23, 24]. Our current study once again demonstrated that CID patients had SWM and ORcM impairments (see Table 2), consistent with our previous findings [5,12]. Nevertheless, little is known about the mechanism of memory impairment in the CID patients.…”
Section: Discussionsupporting
confidence: 89%
“…It is sensitive to the deficits of visuo-spatial memory [9]. Consistently, our previous studies showed that the modified Nine Box Maze Test can detect mild-damaged spatail working memory (SWM) and object recognition memory (ORcM) [5,12] or and object working memory (OWM) [12] in the CID patients or SWM, OWM and spatial reference memory (SRM) in the chronic tensiontype headache patients [13]. However, the mechanisms of objectively special-impairment memories in the CID patients have not been known well.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…It has been demonstrate that acute physical exercise is linked with insomnia symptoms via cortisol levels since the contents of this hormone have been found increased after acute high-intensity training [26,27]. An elevated cortisol levels in the evening correlate with the number of bouts of nocturnal awakenings in insomnia patients [28]. However, chronic moderate aerobic exercise using treadmill with an initial velocity of 4 km/h, increasing speed by 0.5 km/h each minute until voluntary exhaustion (3 times/week/4 months) decreased the cortisol levels, reduced sleep onset latency, and significantly increased total sleep time [29].…”
Section: Physical Exercisementioning
confidence: 99%